Pharmacotherapy of Insomnia with Ramelteon: Safety, Efficacy and Clinical Applications - Pandi Perumal, Seithikurippu R. (2011)
Ramelteon is a tricyclic synthetic analog of melatonin that acts specifically on MT1 and MT2 melatonin receptors. Ramelteon is the first melatonin receptor agonist approved by the Food and Drug Administration (FDA) for the treatment of insomnia characterized by sleep onset difficulties. Ramelteon is both a chronobiotic and a hypnotic that has been shown to promote sleep initiation and maintenance in various preclinical and in clinical trials. The efficacy and safety of ramelteon in patients with chronic insomnia was initially confirmed in short-term placebo-controlled trials. These showed little evidence of next-day residual effects, withdrawal symptoms or rebound insomnia. Other studies indicated that ramelteon lacked abuse potential and had a minimal risk of producing dependence or adverse effects on cognitive or psychomotor performance. A 6-month placebo-controlled international study and a 1-year open-label study in the USA demonstrated that ramelteon was effective and well tolerated. Other potential off-label uses of ramelteon include circadian rhythm sleep disorders such as shift-work and jet lag. At the present time the drug should be cautiously prescribed for short- term treatment only.